ANALYSIS THE INFLUENCE OF VARIATION SHEAR REINFORCEMENT SPACING IN REINFORCED CONCRETE BEAM TESTING - Tampubolon, Sudarno P; Antonius, Dikky (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Beams are crucial components of a building structure that require attention during the design phase. Several failures in beams occur due to inadequate installation of reinforcement according to the planned procedures or designs, which can lead to structural failures. Based on the analysis and testing of three reinforced concrete beams B1, B2, and B3 conducted in the laboratory, the maximum axial compressive strength obtained is 125 kN and the flexural tensile strength is 5.56 MPa. The deflection values observed for beam B1 7.05 mm, beam B2 8.4 mm, and beam B3 18.75 mm. The crack widths observed for beam B1 range from 0.1 to 0.4 cm, beam B2 range from 0.1 to 5 cm, and beam B3 range from 0.1 to 12 cm. Deflection values and crack patterns/failure modes observed in reinforced concrete beams B1, B2, and B3, it is evident that the most significant failure patterns occur in Beam B3 with a stirrup spacing @200mm compared to stirrup spacings @100mm and @150 mm. The use of 45° hooks on stirrups results in diagonal failure in beams. This is attributed to the strong bond between the concrete and the installed reinforcement, thereby interlocking with each other.